Phase angle and extracellular edema predict risk of postoperative complications in total joint arthroplasties - Nguyen Natalie; Marinier Michael C.; Mouser Bryan; Tappa Victoria C.; Rupe Marshall; Elkins Jacob M. (Journal of Electrical Bioimpedance, 2025)
Total knee arthroplasty (TKA) and total hip arthroplasty (THA) are common procedures that improve mobility but carry a risk of postoperative complications, particularly in patients with obesity. Body Mass Index (BMI) is traditionally used for risk assessment but does not account for muscle mass or fat distribution. Bioelectrical impedance analysis (BIA) provides a more detailed body composition evaluation. This study investigates the association between BIA-derived metrics and postoperative complications in TKA and THA, hypothesizing that these metrics are superior predictors compared to BMI.